Clinical significance blood platelet count in patients with chronic hepatitis C on the background of the various options combined antiviral therapy - K. V. Zhdanov; D. A. Gusev; K. V. Kozlov; A. V. Shekurov (Журнал инфектологии, 2014)
The purpose of this research is the study of the dynamics of platelet count in blood of patients with chronic hepatitis C on the background of the combined antiviral therapy with standard or pegylated interferon-α in combination with ribavirin. Prior to treatment, as well as at different stages of combined antiviral therapy were studied absolute numbers of blood platelets in patients with chronic hepatitis C. We determined the relationship between platelet counts at different stages of antiviral therapy and baseline clinical and laboratory parameters (age, sex, body mass index, genotype, level of viremia, ALT, fibrosis), as well as alternative combination therapy. It is established that the significant decrease in platelet count in patients with chronic hepatitis C were observed as during treatment with pegylated or standard interferon-α in combination with ribavirin (38,5% and 16,0%, respectively, p < 0,05). Therapy with pegylated interferon-α treatment as compared with standard interferon-α was accompanied by a more pronounced decrease in platelets, peaking at 8 weeks of treatment (188,4±3,9×109/l). In addition, we observed a direct correlation between the level of blood platelets and rate of sustained virologic response. The study identified prognostic criteria, indicating the possible development of thrombocytopenia on the background of antiviral therapy: BMI < 20kg/m2, age over 45 years.